An effective self-test method for extracting thermal parameters of thermopile IR sensors. (15th May 2022) - Yuan, Tianhui; Fu, Jianyu; Lu, Yihong; Hou, Ying; Huang, Peng; Chen, Dapeng
Highlights: We presented a self-test method based on the thermopile structural model and electrical characteristics to evaluate the thermal parameters of thermopile IR sensors. We measured the Seebeck coefficient, thermal conductance, heat capacitance, and thermal time constant of a thermopile IR sensor, respectively. Compared with the results obtained by other methods, the relative errors are small. This method could provide certain guiding relevance for associated researchers conducting design improvement and performance testing because of its simplicity and effectiveness. Abstract: Thermopile infrared (IR) sensors are thermal-type sensors. It is of great significance to evaluate its four thermal parameters: Seebeck coefficient, thermal conductance, heat capacitance, and thermal time constant. In this work, an effective self-test method to measure these thermal parameters is proposed that takes advantages of thermopile IR sensors' structural and electrical characteristics and does not need to add heater in structure. The technique to accurately extract thermal parameters is analyzed carefully, and its validity is verified by a thermopile IR sensor. The experimental Seebeck coefficient is consistent with the tested value of on-chip test structure in the same die, and the experimental thermal conductance, heat capacitance, and thermal time constant results agree well with the theoretical analysis of structure. These demonstrate that this method is effective and accurate, as well as simple for researchers to apply.